2019
DOI: 10.1186/s40478-019-0678-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of DYRK1A proteolysis modifies its kinase specificity and rescues Alzheimer phenotype in APP/PS1 mice

Abstract: Recent evidences suggest the involvement of DYRK1A (dual specificity tyrosine phosphorylation-regulated kinase 1 A) in Alzheimer’s disease (AD). Here we showed that DYRK1A undergoes a proteolytic processing in AD patients hippocampus without consequences on its kinase activity. Resulting truncated forms accumulate in astrocytes and exhibit increased affinity towards STAT3ɑ, a regulator of inflammatory process. These findings were confirmed in APP/PS1 mice, an amyloid model of AD, suggesting that this DYRK1A cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 50 publications
(55 reference statements)
1
38
0
Order By: Relevance
“…S2 and S3 ). Therefore, previously established concentrations for in vivo treatments of Dyrk1A hyperactivity in Drosophila and mouse were used ( 47 , 48 ). PC-RFP and PC-Dyrk1A zebrafish larvae were treated for four consecutive days either with ProINDY (2.5 μM) or Leucettine L41 (2 μM) starting at 3 dpf when PCs begin to differentiate and express hDyrk1A ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2 and S3 ). Therefore, previously established concentrations for in vivo treatments of Dyrk1A hyperactivity in Drosophila and mouse were used ( 47 , 48 ). PC-RFP and PC-Dyrk1A zebrafish larvae were treated for four consecutive days either with ProINDY (2.5 μM) or Leucettine L41 (2 μM) starting at 3 dpf when PCs begin to differentiate and express hDyrk1A ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DYRK1A inhibition has been proposed as a putative therapeutic strategy in AD, since it reduces APP phosphorylation and has a positive impact on restoring abnormal phenotypes in AD mouse models 7 30 61 62 63 . To study the interaction of DYRK1A and APP we cultured human differentiated neurons to analyze the axonal transport properties of fluorescently labeled APP vesicles after DYRK1A modulation.…”
Section: Discussionmentioning
confidence: 99%
“…DYRK1A contains a PEST sequence, a signal peptide for protein degradation via calpain (101, 102). Recently, Souchet et al found that this DYRK1A cleavage is a consequence of the amyloid pathology (103). Resulting truncated forms accumulate in astrocytes and exhibit increased affinity toward a regulator of inflammatory process (103).…”
Section: Statement Of Hypothesis: Plasma Levels Of Dyrk1a Bdnf and mentioning
confidence: 99%
“…Recently, Souchet et al found that this DYRK1A cleavage is a consequence of the amyloid pathology (103). Resulting truncated forms accumulate in astrocytes and exhibit increased affinity toward a regulator of inflammatory process (103). Here, we analyzed these different forms by the use of two different antibodies, one recognizing the full-length form, and the other the full-length and truncated forms of Dyrk1A (Figure 2A) in plasma of control Wistar (WT) and GK rats.…”
Section: Statement Of Hypothesis: Plasma Levels Of Dyrk1a Bdnf and mentioning
confidence: 99%